2020
DOI: 10.1002/inf2.12095
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of coupled valley and spin Hall effect in p‐doped WSe2 devices

Abstract: Giant spin Hall effect (GSHE) has been observed in heavy metal materials such as Ta, Pt, and W, where spins are polarized in the surface plane and perpendicular to the charge current direction 1-3 . Spins generated in these materials have successfully switched magnets with in-plane magnetic anisotropy (IMA) and perpendicular magnetic anisotropy (PMA) through spin orbit torque (SOT) mechanism. It is generally accepted that PMA magnets are preferred over IMA magnets in data storage applications owing to their la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Since the discovery of graphene, two-dimensional (2D) materials have demonstrated extremely impressive mechanical, electronic and optoelectronic properties of mechanical exibility, adjustable bandgap and strong light-matter interactions. [1][2][3][4][5][6][7][8][9][10][11][12][13] With the booming development of the 2D metal suldes, multiphase In 2 S 3 has attracted extensive attention and been used for high-performance applications in photodetectors, phase change memory devices and catalysis. [14][15][16][17] There are three main crystalline structures of a-In 2 S 3 , b-In 2 S 3 , and g-In 2 S 3 which have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of graphene, two-dimensional (2D) materials have demonstrated extremely impressive mechanical, electronic and optoelectronic properties of mechanical exibility, adjustable bandgap and strong light-matter interactions. [1][2][3][4][5][6][7][8][9][10][11][12][13] With the booming development of the 2D metal suldes, multiphase In 2 S 3 has attracted extensive attention and been used for high-performance applications in photodetectors, phase change memory devices and catalysis. [14][15][16][17] There are three main crystalline structures of a-In 2 S 3 , b-In 2 S 3 , and g-In 2 S 3 which have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In these reports, an out-of-plane spin/valley polarization of 70% was observed at the edges of p-doped monolayer WSe 2 due to VHE [27]. A similar electrically generated interfacial spin polarization of 38% was also observed in WSe 2 /graphene heterostructure [23]. Spin-valley locked states in TMDs are also long-lived [28,29] with large out-of-plane spin diffusion lengths of hundreds of nanometers [25].…”
mentioning
confidence: 71%
“…Spinresolved photoemission spectroscopy measurements have revealed valley-dependent out-of-plane spin polarized valence states in TMDs [18][19][20][21][22]. Subsequently, transport experiments unambiguously demonstrated that a flow of out-of-plane spins in WSe 2 monolayers can be electrically generated through the valley Hall effect (VHE) [23], a topological Hall response driven by the finite and opposite Berry curvatures in the two valleys [23][24][25][26][27]. In these reports, an out-of-plane spin/valley polarization of 70% was observed at the edges of p-doped monolayer WSe 2 due to VHE [27].…”
mentioning
confidence: 99%
“…The intervalley scattering of holes in WSe 2 must also flip spin, resulting in a prolonged spin and valley lifetime . While all-electrical measurements of the spin or valley Hall effect have been performed at room temperature, it is a challenge to distinguish the SVHE non-local electrical signal from other potential sources, including a variety of unclear effects that are unrelated to spin and valley, similar to those reported in previous works on graphene. Optical measurements of electrically generated SVHE, on the other hand, can directly image the spatial distribution of the polarization and can be used to extract more parameters. Previous work has demonstrated, via spatial Kerr rotation (KR) measurements, the observation of the SVHE in n-type bilayer and monolayer MoS 2 and in p-type monolayer WSe 2 FETs at temperatures from 20 to 30 K. However, little work has shown electrical control of the SVHE, and detailed interpretation of the SVHE-induced KR data and the study of the temperature and carrier density dependence of SVHE parameters are sorely lacking.…”
Section: Introductionmentioning
confidence: 99%